08.44 Clinical and immunological characteristics of antiphospholipid syndrome in patients with incomplete systemic lupus erythematosus. (1st March 2017) - Monov, Simeon; Monova, Daniela; Shumnalieva, Russka; Rashkov, Rasho; Baleva, Marta
Abstract : Abstract: The aim of our study is to investigate the features of the clinical course and the immunological characteristics of anti-phospholipid syndrome (APS) in patients with incomplete systemic lupus erythematosus (SLE). Material and methods: 58 patients (aged from 19 to 39 years, mean age 28.57±5.37 years) with incomplete SLE according to the 1997 update of the 1982 American College of Rheumatology Revised Criteria for classification of SLE were included in the study. 53 of them were women and 5 men (sex ratio 10.6:1) and the disease duration was between 1 and 8 years (mean disease duration 3.29±1.27 years). Clinical, immunological and instrumental investigations were performed in all patients. The disease activity (DA) was determined by SLE DA index (SLEDAI) with 24 descriptors. Results: APS was found in 12 (6.96%) of the studied patients. The main clinical features of APS in the studied patients with incomplete SLE were: pulmonary infarctions – in 2 (16.67%), peripheral thrombosis (a/v) – in 5 (41.67%), miscarriages/stillbirths – in 10 (83.33%). The mean immunological abnormalities were: positive aCL – in 12 (100%), positive a-β2 GP1 – in 2 (16.67%), and positive LAC – in 5 (41.67%). Thrombocytopenia was found in 10 of the patients (17.24%). Conclusion: 1. In patients with incomplete SLE there was a variety of systemic abnormalities; 2. According to the criteria of SLE the incomplete SLE may have a high disease activity; 3. Adding the anti-phospholipid antibodies to the diagnostic criteria of SLE is a reason some of the patients with incomplete SLE to be diagnosed as having complete SLE.